Balancing productivity and trade objectives in a competing environment: Should India commercialize GM rice with or without China? - Gruère, Guillaume P.; Mevel, Simon; Bouët, Antoine (Wiley, 2009)
India is considering approving genetically modified (GM) rice, but it fears losing rice exports to sensitive countries with import regulations on GM food, and may wait for China to lead the way. Using a multiregion, computable general equilibrium (CGE) model, we simulate the economic effects of introducing GM rice in India with or without China in the presence of labeling and import approval regulations of GM food in GM sensitive importing countries. We find that the welfare gains with GM rice in India would largely exceed any potential export loss, and that the segregation of non‐GM rice could help reduce these minor losses. We also find no significant first mover advantage for India or China on GM rice. The opportunity cost of segregation of non‐GM rice is much larger for sensitive importers than for India, which suggests that these importers would have the incentive to pay for the cost of segregation.